Plan de negocio para exportación de conservas de fréjol castilla para Brasil - Chillcce Chaparro, Lidia (2017)
This paper “PLAN DE NEGOCIO PARA EXPORTACIÓN DE CONSERVAS DE FRÉJOL CASTILLA PARA BRASIL”, consists in the elaboration of a Business Plan for Exports of Canned Black-eyed beans or Black-eyed peas for Brazil, this business is dedicated to the collection, processing, packaging and export of beans. It is mainly based on the increasing of production and exports of Black-eyed peas in Peru and at the same time the increasing of its consumption in the Brazilian market. The black-eyed pea nutritional characteristics and health benefits are focused. It also does all a market analysis which involves the behavior of Brazilian consumers, per capita income, competition, the international export mechanisms and regulations necessary to enter this market. Finally, we develop the financial viability of the project in which projections were made for the early years of operation and expected rates of return.